Linking land use and forestry transition with depopulation in rural Nepal - Poudel, M.; Kafle, G.; Khanal, K.; Dhungana, S.; Oli, B. N.; Dhakal, A.; Acharya, U. (Banko Janakari, 2018)
Migration borne depopulation has been emerging as a new dimension of conservation challenges. Existing body of knowledge, however, lack in-depth understanding of this emerging dynamics of depopulation and its forestry implications. Aiming to analyze implications of migration borne land use transition, this study investigated the nature and impacts of migration in rural communities involved in managing community forestry and other tree resources This study was grounded in the experiences and perceptions of community forest users groups in Parbat and Lamjung districts and applied a pragmatic approach to social science, involving the collection of both qualitative and quantitative data. A total of 218 semi-structured interviews, two focus group discussions and three stakeholders’ consultations were conducted. Spatial changes in land use were analyzed using Landsat images of 2000 and 2016 and other existing land use maps.The study found decreasing trend of population growth and identified out-migration of local youth as the main driver. Identified underpinning causes motivating for migration include desire of higher education, employment and resettlement, poverty and poor access to education, markets and other opportunities. This study found negative correlation between migration and farming activities but positive correlation between forest and tree coverage. Forests and other woodland increased but none forest area, most of which were farmlands, decreased. Community forests were getting denser but they lack proper management, abandoned farmlands were turning into bushes, which have increased the risk of forest fire. This study showed very poor understanding of REDD+ and related issues at community level and suggests substantial gaps in policies and procedures to translate migration borne land use transition into opportunities for generating multiple benefits including carbon finance as an additional benefit. Banko Janakari A Journal of Forestry Information for Nepal Special Issue No. 4, 2018, Page: 130-143